2019
DOI: 10.3390/su11112998
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Change Management through Employee Readiness: Decision Support System Adoption in Technology-Intensive British E-Businesses

Abstract: Technology brings green sustainable management practices to the workplace. It is important to ascertain the factors that enable or inhibit employees' perceptions towards technology adoption. Corporate sustainability and sustainable management practices partially depend on employees for the successful implementation of technological changes in the workplace. This study aims at applying the technology acceptance model (TAM) from an employees' user-perspective. It addresses those factors that form employee readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…The role of employees in successful technology implementation is of primary importance because the user’s acceptance is a critical aspect in an organization ( Ahmed et al, 2019 ; Scherer et al, 2019 ). IS extends a positive experience accumulation amongst employees leading to positive attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of employees in successful technology implementation is of primary importance because the user’s acceptance is a critical aspect in an organization ( Ahmed et al, 2019 ; Scherer et al, 2019 ). IS extends a positive experience accumulation amongst employees leading to positive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…While reviewing the relevant literature, it has been observed that numerous personality traits have been studied for their effect on the technology adoption by individuals in varying backgrounds and contexts such as insecurity, optimism, discomfort, innovativeness, self-efficacy, trust, and perceived risk, etc. ( Liljander et al, 2006 ; Erdoǧmuş and Çiçek, 2012 ; Lai et al, 2012 ; Ahmed et al, 2019 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish mediation, the significance of the direct, indirect effect and total effect needs to be assessed [93,94]. In this research, direct effect is the value of path coefficient (β) from servant leadership to EVGB.…”
Section: Mediation Analysismentioning
confidence: 99%
“…Management processes are costly in themselves, they influence the creation of the final product, the quality of which determines the level of income of the enterprise. The use of information technologies in planning business activities and increasing its sustainability has become extremely important [4][5][6][7][8][9][10][11][12]. Thus, their indirect impact on the direct processes of the main activities on the one hand does not allow the direct method to take into account the costs incurred, and on the other requires an assessment of the quality level of the impact to highlight the bottlenecks in the main processes.…”
Section: Introductionmentioning
confidence: 99%